2019
DOI: 10.1111/vec.12851
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the association between admission blood glucose and l‐lactate concentrations in ponies and horses with gastrointestinal disease (2008‐2016): 545 cases

Abstract: Objectives A recent study described increased l‐lactate concentrations in ponies with gastrointestinal disease compared to horses, but blood glucose (BG) concentrations were not considered. The study tested the hypothesis that BG and l‐lactate concentrations are correlated in horses and ponies with gastrointestinal disease and that BG concentrations, not equid type (pony vs horse), are an independent predictor of L‐lactate concentrations. It was further hypothesized that equid type was an independent predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
1
16
2
Order By: Relevance
“…Similar to previous studies, ponies compared to horses had higher average BCS and higher heart girth:height and lower neck length:heart girth ratios, indicating that adiposity was more widespread in ponies. Contrary to expectations and in contrast to previous studies in horses and ponies with gastrointestinal disease, healthy ponies had significantly lower blood l ‐lactate concentrations compared to horses. l ‐lactate concentrations were weakly, but significantly, associated with measures of adiposity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar to previous studies, ponies compared to horses had higher average BCS and higher heart girth:height and lower neck length:heart girth ratios, indicating that adiposity was more widespread in ponies. Contrary to expectations and in contrast to previous studies in horses and ponies with gastrointestinal disease, healthy ponies had significantly lower blood l ‐lactate concentrations compared to horses. l ‐lactate concentrations were weakly, but significantly, associated with measures of adiposity.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent studies investigating ponies and horses with gastrointestinal disease, blood l ‐lactate and glucose concentrations on admission were higher in ponies compared to horses regardless of the primary lesion . The investigators speculated that ponies could have higher resting l ‐lactate concentrations either as a result of differences in body condition (BC), particularly obesity, or underlying metabolic differences such as a comparatively lower insulin sensitivity in ponies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between full-sized horses and ponies in glucose and insulin metabolism, oxidative capacity and response under sympathetic stimulation are widely reported in the literature [21-23, 35, 45]. Although higher glucose concentrations, re ecting metabolic differences have been clearly shown in ponies with gastrointestinal diseases [45], these differences are frequently not noticeable at rest but only during dynamic response testing [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…12 This difference may be explained by carbohydrate metabolism via the Cori cycle, in which blood glucose (which also was found to be higher in the study ponies) leads to the generation of lactate. 13 Increased liver enzyme activities occasionally are observed in horses presented for acute gastrointestinal disorders and likely reflect anatomic proximity of the 2 organ systems and direct communication via the biliary system and portal circulation. A retrospective study examining horses with colic observed that increased g-glutamyltransferase (GGT) activity was observed in 49% of horses with right dorsal displacement but only 2% of horses with left dorsal displacement of the large colon, a finding attributed to extrahepatic biliary obstruction from bile duct compression by the displaced colon.…”
Section: Acute Gastrointestinal Diseasementioning
confidence: 99%